War, coups & terror : Pakistan's army in years of turmoil - Cloughley, Brian (New York, NY : Skyhorse Pub., 2008)
A major study on the Pakistan army discusses the Pakistan military's controversial role in government, its position as a force in the fight against al-Qaeda and the Taliban, and operations against the 2003-2004 tribal uprising.
Zulfikar Ali Bhutto -- The years of Zia -- Democracy again -- Karamat, Kargil, chaos -- The coup, the borders and the Army's capabilities -- How the Army looks after its own -- The modern Army and its challenges -- Terrorism and tribes -- Pakistan in danger.
Includes bibliographical references and index.
Keywords: Pakistan. -- Army -- History; Pakistan. -- Army -- Influence; Coups d'état -- Pakistan -- History; Terrorism -- Pakistan -- History; Civil-military relations -- Pakistan; Pakistan -- History, Military; Pakistan -- Politics and government; Pakistan -- Military policy; Pakistan -- Strategic aspects